Tylna niedokrwienna neuropatia nerwu wzrokowego jako powikłanie obustronnej radykalnej operacji usunięcia węzłów chłonnych szyi - Obuchowska, Iwona; Mariak, Zofia; Budrowski, Radosław (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Visual loss is a rare and potentially devastating complication of surgery under general anesthesia. We present a case of blindness after simultaneous bilateral neck dissection and discuss the perioperative circumstances and the possible causes. We also compare and contrast other such cases described in the literature and remind the clinical criteria for the diagnosis of perioperative type of posterior ischemic optic neuropathy.